2022
DOI: 10.1097/md.0000000000028810
|View full text |Cite
|
Sign up to set email alerts
|

Two cases of fatal methemoglobinemia caused by self-poisoning with sodium nitrite

Abstract: Rationale:Sodium nitrite intoxication reportedly causes severe methemoglobinemia. Recent studies reported that most clinically significant cases resulted from intentional exposure in suicidal attempts. We describe 2 cases of severe methemoglobinemia secondary to intentional sodium nitrite intoxication in suicidal attempts.Patients concerns:A 26-year-old man and 20-year-old woman attempted suicide by taking sodium nitrite, and were brought to the emergency department.Diagnosis:The male patient collapsed at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…The 6 patients with intentional nitrite use all received methylene blue therapy. Increases in suicide attempts with sodium nitrite have been reported to be increasing, in part due to online information on its toxic effects coupled with availability of this compound through internet sources [37] , [53] , [54] , [55] . A set of twin infants had life-threatening methemoglobinemia from food contaminated with nitrates in a case investigated by public health authorities; both infants were treated with methylene blue [46] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 6 patients with intentional nitrite use all received methylene blue therapy. Increases in suicide attempts with sodium nitrite have been reported to be increasing, in part due to online information on its toxic effects coupled with availability of this compound through internet sources [37] , [53] , [54] , [55] . A set of twin infants had life-threatening methemoglobinemia from food contaminated with nitrates in a case investigated by public health authorities; both infants were treated with methylene blue [46] .…”
Section: Discussionmentioning
confidence: 99%
“…However, in clinical practice, methemoglobinemia is more commonly the result of exposure to one or more exogenous substances [1] , [10] . Many causal substances have been identified, including benzocaine and other topical anesthetics [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , dapsone (anti-infective used for treatment of leprosy, dermatitis herpetiformis, and Pneumocystis jirovecii ) [10] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , antimalarial agents (e.g., chloroquine) [1] , [24] , nitric oxide [30] , [31] , and nitrites [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] ( Table 1 ). Dietary nitrates and nitrites in food and drinking water is a major cause of methemoglobinemia in some parts of the world [10] , [33] , [40] , [41] .…”
Section: Introductionmentioning
confidence: 99%
“…Fatal cases of voluntary intoxication via the use of suicide kits have recently been reported in the literature [1, 3–11].…”
Section: Discussionmentioning
confidence: 99%
“…9 Case reports from the US, Japan, and Korea have also confirmed that sodium nitrite is being ingested as a means of suicide. [19][20][21][22][23][24][25] In 2022, researchers surveyed this literature for cases of sodium nitrite ingestion. 11 Their review identified 132 cases, 53 of which were for suicidal purposes.…”
Section: Statisticsmentioning
confidence: 99%